IKM 2019
DOI: 10.7176/ikm/9-2-06
|View full text |Cite
|
Sign up to set email alerts
|

The Capability and Support of Structure Capital on BIM Innovation in SME

Abstract: The Architecture, Engineering, and Construction (AEC) industry has been changing over the years with the emergence of BIM. The small and medium sized enterprises are not left out of the change, bringing distortion to their business environment and process. Extant studies have revealed that Structure Capital (SC) is an integral part of the innovative capacity of firms, this study examines the capability of SC on Architectural SME firms in Nigeria. The research was designed in three stages, empirical enquiry, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…BIM studies in SMEs are underrepresented in the literature and the majority of the extant studies are from developed economies (Saka and Chan, 2021). Kori et al. (2019) revealed that the SMEs in the Nigerian AEC are slower to adopt BIM adoption compared to large firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…BIM studies in SMEs are underrepresented in the literature and the majority of the extant studies are from developed economies (Saka and Chan, 2021). Kori et al. (2019) revealed that the SMEs in the Nigerian AEC are slower to adopt BIM adoption compared to large firms.…”
Section: Literature Reviewmentioning
confidence: 99%